2017
DOI: 10.3357/amhp.4595.2017
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Changes in the Perception of Fast and Slow Movement at Different Head Positions

Abstract: This difference between on-vertical and off-vertical axis rotation was probably partly due to the vestibular transfer function and partly due to different adaptation to the speed of rotation. Such a phenomenon might be generated in different components of the vestibular system. The adaptive process enhancing the perception of dynamic movement around the vertical axis is not related to the specific semicircular canals that are activated; the addition of an otolithic component results in a significant increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Thus, the walking directional shift observed in our study cannot be directly related with a shift of the SSA. However, taking into account previous studies emphasizing adaptational mechanisms on both perceived direction of gravity ( 10 , 14 ) and self-motion perception ( 19 , 20 ) by prolonged (asymmetric) otolith stimulation, such a direct mechanism seems less likely.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, the walking directional shift observed in our study cannot be directly related with a shift of the SSA. However, taking into account previous studies emphasizing adaptational mechanisms on both perceived direction of gravity ( 10 , 14 ) and self-motion perception ( 19 , 20 ) by prolonged (asymmetric) otolith stimulation, such a direct mechanism seems less likely.…”
Section: Discussionmentioning
confidence: 93%
“…With eyes closed, strong ipsilesional walking deviations ( 16 , 17 ) and ipsilesional whole-body rotational deviations when walking on the spot ( 18 ) have been observed. Furthermore, it has been shown that the repetitive one side predominant asymmetric (off-vertical axis) stimulation of the vestibular system influences the spatial representation of the subjective straight-ahead (SSA) and self-motion perception in the opposite direction of the most rapid stimulus ( 19 , 20 ), emphasizing a significant otolithic component in this paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Since the aromatase in the cerebellum and brainstem in rodents has very similar expression to that detected in humans, one can also hypothesize similar vestibulo-cerebellar mechanisms controlled by nE2 and leading to motor learning in these two species [66,79,80,83]. A cardinal consequence that extends this concept is that nE2 could influence human perceptive and motor phenomena that require adaptive process and plasticity in the vestibulo-cerebellar networks in physiological as well as pathological conditions [172][173][174][175][176]. Thus, nE2 may exert its influence not only on VOR adaptation but even on the rebalancing after labyrinthine lesion of vestibular reflexes and perception [177][178][179] and on other motor behaviors like balance and locomotion requiring the computational power of cerebellar networks to adapt responses to the context [120,128,180,181].…”
Section: Implications For the Impact Of Ne2 On The Cerebellar Functionmentioning
confidence: 86%
“…Although our results are specific for the VOR, the finding that behavior depending on cerebellar–vestibular plasticity is responsive to Ars inactivation has relevance for the potentially broad impact that androgens may exert in controlling cerebellar–vestibular functions. Besides VOR adaptation, androgens could influence processes that require adaptive phenomena and plasticity in cerebellar–vestibular networks in physiological as well as pathological conditions, including the rebalancing of vestibular reflexes and perception after labyrinthine lesion or intense stimulation (Dutia, 2010; Panichi et al., 2011; Panichi, Faralli, et al., 2017; Panichi, Occhigrossi, et al., 2017; Pettorossi et al., 2015; Pettorossi, Panichi, et al., 2013; Scarduzio et al., 2012; Smith et al., 2019) and other motor learning involving balance, locomotion, and arm movement (Ito, 2013; Manto & Oulad Ben Taib, 2013; Morton & Bastian, 2004; Sokolov et al., 2017). Moreover, androgens could more widely impact motor and nonmotor functions via influencing the cerebellum.…”
Section: Discussionmentioning
confidence: 99%